2010
DOI: 10.1002/ieam.116
|View full text |Cite
|
Sign up to set email alerts
|

Application of the tissue residue approach in ecological risk assessment

Abstract: The objective of this work is to present a critical review of the application of the tissue residue approach (TRA) in ecological risk and/or impact assessment (ERA) of chemical stressors and environmental criteria development. A secondary goal is to develop a framework for integrating the TRA into ecological assessments along with traditional, exposure concentration-based assessment approaches. Although widely recognized for its toxicological appeal, the utility of the TRA in specific applications will depend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 72 publications
0
39
0
Order By: Relevance
“…Despite the widespread occurrence of CECs and importance whole-body tissue concentration in risk assessment and regulatory frameworks (Sappington et al 2011), we found no comprehensive studies reporting on whole-body tissue concentrations for these compounds in field-collected fish. Clearly, this is an important data gap in assessing the environmental risk of CECs.…”
Section: Discussionmentioning
confidence: 91%
“…Despite the widespread occurrence of CECs and importance whole-body tissue concentration in risk assessment and regulatory frameworks (Sappington et al 2011), we found no comprehensive studies reporting on whole-body tissue concentrations for these compounds in field-collected fish. Clearly, this is an important data gap in assessing the environmental risk of CECs.…”
Section: Discussionmentioning
confidence: 91%
“…CSA is the primary method for assessing risk to wildlife and for deriving criteria for protection of wildlife (CCME 1998 ;US EPA 1995a, b, 2003, 2005Sample and Suter 1993 ) . This method is used to select the critical study for deriving recommended TRVs, which involves fi nding a technically defensible, de fi nitive study from which a toxicity threshold is bracketed by experimental doses (Blankenship et al 2008 ;US EPA 2003 ) .…”
Section: Methods Of Deriving Trvs and Trcsmentioning
confidence: 99%
“…For metals, the application of whole-body residues as threshold criteria associated with effects does not lead to a defensible prediction of risk to the organism largely due to the existence of metal-and species-specific physiological mechanisms that facilitate acclimation to metal exposure . Sappington et al (2011) present a critical review of the application of the TRA in approach in ecological risk assessment and environmental criteria development. Those authors proposed that rather than supplanting exposure concentration-based toxicity assessments, the TRA can be highly effective for evaluating and reducing uncertainty when used in a complementary manner, as one among multiple lines of evidence in field studies.…”
Section: Measuring and Interpreting Bioaccumulationmentioning
confidence: 99%
“…For example, many authors now advocate that laboratory toxicity testing be performed concurrently with physicochemical characterizations, indigenous biotic community assessment and in situ-based approaches to characterize exposures from overlying waters, sediments and advective groundwater-pulse events (Burton, 1991;Burton et al, 2005a;Greenberg et al, 2002;Adams et al, 2005). Sediment quality assessment tools and approaches also include toxicity identification evaluations (TIEs) (USEPA, 2007;Ho and Burgess, 2009), assessment of abiotic factors as stressors (Burton and Johnston, 2010) and toxicological evaluation of tissue residue (Meador et al, 2008;Sappington et al, 2011). However, compartmentalization rather than integration of key approaches and issues is a potential pitfall for sediment quality evaluation.…”
Section: Introductionmentioning
confidence: 99%